Comparison of standard‐based and standardless methods of quantification used in X‐ray fluorescence analysis: Application to the exoskeleton of clams. (6th November 2017) - Pessanha, S.; Fonseca, C.; Santos, J.P.; Carvalho, M.L.; Dias, A.A.
Abstract : In this work, we aim at achieving the most accurate quantitative determination of the composition of exoskeletons of bivalves from Tagus estuary with Energy Dispersive X‐ray Fluorescence. Samples from the shells of clams ranging from the Bronze Ages to the 16th century A.D . belonging to the Museu Arqueológico de Almada, and also from the shells of clams collected recently in the same region, were analyzed for comparison of the trace element composition and detection of heavy metals. The analysis was performed with 2 Energy Dispersive X‐ray Fluorescence setups, one with triaxial geometry and another with a conventional geometry and vacuum capabilities. Samples were pressed as pellets, and the spectra collected with both setups were evaluated using standardless fundamental parameter based software's implemented in each setup, and by comparing with standard reference materials of similar matrix. The comparison of the results obtained with different methods lead to the conclusion that the most realistic results were obtained with calibration curves obtained with external standards and correction the fluorescent intensities with the Compton scattering peak. When comparing the obtained concentrations for all the analyzed periods, results showed a decrease of Fe in the 12th Century. Regarding the environmental current state of the Tagus estuary, there were no heavy metals detected above the safety regulations.